De la « Fortress Conservation » aux nouveaux modèles de gestion participative de la biodiversité en Tanzanie - Adriana Blache (VertigO)
This article analyses the new models of biodiversity conservation in Tanzania as an "apparatus" that is accompanied by a rhetorical arsenal legitimizing the removal of villages or significant parts of village land. Taking as a starting point the constancy of the exotico-colonial imagination in Western representations of biodiversity in Tanzania, the article raises the question of the legitimacy of so-called "illegal" forest occupations as a result of what could be described as environmental injustices. Conservation models with a "participatory and inclusive" label are more related to the criminalization of practices and uses prior to the devices and promote the multiplication of guards and police, rather than proposing a particular awareness within a broader vision of political ecology. While the stated objective of so-called participatory models is to go beyond "fortress conservation", they accentuate land conflicts in the interstices of conservation areas. Despite the international financial flows that irrigate the development and environmental conservation projects, the resistance engaged by the occupants, who have become "illegal" contrasts with the technical and depoliticized rationality of the imposed maps and borders.